The Influence of Organizational Culture, Professional Commitment and Level of Religiosity to Ethical Judgement of the Auditor: Indonesia Evidence - Yudhistira, Rio Arief; Habiburochman, Habiburochman (The Indonesian Journal of Accounting Research, 2017)
Abstract: The purpose of the research is to obtain empirical evidence about the impact of organizational culture, professional commitment and religiosity to ethical judgment of the auditor. The study was conducted by-administered questionnaire distribution model that applied to all the auditors who work in Public Accounting Firm (HOOD) in Surabaya. The sample in this research is 86 auditors from 18 Public Accounting Firm. Hypothesis testing  was being done using PLS. The study found that organizational culture effect positively to the auditor's ethical judgment but facial took. While Auditors' commitment professional and the auditor's religiosity level effect positively significant to the auditor's ethical judgmentAbstrak: Tujuan dari penelitian ini adalah untuk memperoleh bukti empiris tentang dampak budaya organisasi, komitmen profesional dan religiusitas terhadap penilaian etika auditor. Penelitian dilakukan dengan menggunakan model distribusi kuesioner yang diterapkan pada semua auditor yang bekerja di Kantor Akuntan Publik (HOOD) di Surabaya. Sampel dalam penelitian ini adalah 86 auditor dari 18 Kantor Akuntan Publik. Pengujian hipotesis sedang dilakukan menggunakan PLS. Studi ini menemukan bahwa budaya organisasi berpengaruh positif terhadap penilaian etis auditor tetapi pengambilan wajah. Meskipun komitmen profesional Auditor dan tingkat religiusitas auditor berpengaruh positif signifikan terhadap penilaian etis auditor